IFC Annual Report 2019 : Investing for Impact - International Finance Corporation (Washington, DC: International Finance Corporation, 2019)
IFC, a member of the World Bank Group, is the largest global development institution focused on the private sector in developing countries. Established in 1956, IFC is owned by 185 member countries, a group that collectively determines our policies. We leverage our products and services—as well as those of other institutions across the World Bank Group—to create markets that address the biggest challenges of our time that developing countries face. We apply our financial resources, technical expertise, global experience, and innovative thinking to provide sustainable market-based solutions that bring widespread benefits. IFC is also a leading mobilizer of third-party resources for projects. Our willingness to engage in difficult environments and our leadership in crowding in private finance enable us to have a development impact well beyond our direct resources.